Comparison of Xpert® Breast cancer STRAT4 assay and immunohistochemistry for the evaluation of breast cancer biomarkers in South African patients - Dube, Welile Vumile (Stellenbosch : Stellenbosch University, 2020)
Thesis (MMed)--Stellenbosch University, 2020.